The Relationship Between Educators' Teaching Strategies and the Moral Development of Children Aged 4-5 Years in PAUD Amanah Kota Pariaman - Yunia, Vera; Ismaniar, Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research is motivated by the low moral development of children, this is thought to be caused by the inappropriate strategies used by educators in teaching. This research aims to describe educators' teaching strategies in developing children's morals at PAUD Amanah Kota Pariaman. Describes the moral development of children aged 4-5 years at PAUD Amanah Kota Pariaman. Seeing the relationship between educators' teaching strategies and the moral development of children aged 4-5 years at PAUD Amanah Kota Pariaman. This research uses a quantitative approach with a correlational type. The population of this study was parents whose children attended PAUD Amanah Kota Pariaman, totaling 24 people. The sampling technique used cluster random sampling, taking 80% of the population, namely 19 people. The data collection technique uses a questionnaire in the form of a list of statements. Data analysis techniques use percentages and rank order. The results of this research indicate that the strategies used by educators in teaching at PAUD Amanah Kota Pariaman are categorized as inappropriate. The moral development of children aged 4-5 years at PAUD Amanah Kota Pariaman is categorized as low. There is a significant relationship between educators' teaching strategies and the moral development of children aged 4-5 years at PAUD Amanah Kota Pariaman. It is recommended that educators use more appropriate teaching strategies and attract children's attention in developing children's moral behavior.